[An Optimal Unemployment Rate: Comment]: Reply - Dobell, A. R. (Quarterly Journal of Economics, 1969)
Journal Article An Optimal Unemployment Rate: Reply Get access A. R. Dobell A. R. Dobell University of Toronto Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 83, Issue 3, August 1969, Pages 521–523, https://doi.org/10.2307/1880537 Published: 01 August 1969